(untitled) (Research, Society and Development, 2020)
The Scientific Literacy (SL) must develop the individual’s ability to organize a logical thinking, besides helping to build a critical consciousness about the world around them. Thereby, this text has a goal to analyze evidence of Scientific Literacy during an Investigative Teaching Sequence (ITS) held at a Science Club in the Amazon. The methodology has the qualitative approach with participant research characteristic. The results showed that it is possible to perceive signs of SL from an ITS activity in this space, for that, it turned to the theoretical framework to give meaning to the interpretation. Therefore, as a conclusion, it was possible to perceive that SL in many moments it’s close to ITS, since it related the seven stages of the process in a subjective way, inferring that during this process there were elements that allowed to relate to Scientific Literacy, mostly when it’s considered the promotion of argumentation as a determining element of this process.